Cryptic species and co‐diversification in sand scorpions from the Karakum and Kyzylkum deserts of Central Asia. (25th September 2019) - Graham, Matthew R.; Myers, Edward A.; Kaiser, Ronald C.; Fet, Victor
Abstract: Little is known about species diversification within the deserts of Central Asia. For example, the degree of lineage divergence and timing of population differentiation, as well as potential biogeographic barriers driving diversification, are nearly unknown. Here, we analysed a multi‐locus data set for a widespread sand scorpion ( Mesobuthus gorelovi ) to evaluate cryptic species diversity and phylogeographic patterns across the Karakum and Kyzylkum deserts. We also combined these data with previously published sequence data to test for a signal of co‐diversification. A consensus species delimitation approach indicated that the widespread M. gorelovi is likely composed of up to five distinct species that began to diversify at the Miocene–Pliocene boundary. We observed shared patterns of lineage divergence across the Amu Darya River region in three scorpion taxa and found support for a shared history of assemblage diversification across this biogeographic barrier. Thus, major river systems appear to facilitate diversification among desert scorpions.